PENGARUH MUTU PELAYANAN, LOKASI DAN DESAIN INTERIOR TERHADAP KEPUTUSAN MENGINAP DI HOTEL LATANSA BENGKULU - Aji Bio Sanjaya (UM. Bengkulu, 2022)
This study aims to 1) The effect of service quality on the decision to stay at the Latansa Hotel Bengkulu. 2) The influence of location on the decision to stay at the Latansa Hotel Bengkulu. 3) The influence of consumer interior design on the decision to stay at the Latansa Hotel Bengkulu. 4) The influence of service quality, location and consumer interior design on the decision to stay at the Latansa Hotel Bengkulu. This type of research is a quantitative approach. The method used in this study is a descriptive method. The population in this study were all consumers of Hotel Latansa Bengkulu. Based on the results of research on the influence of service quality, location and interior design on the decision to stay at the Latansa Hotel Bengkulu. The quality of service has a positive effect on the customer's decision to stay at the Latansa Bengkulu Hotel, thus the higher the service quality, the higher the customer's decision to stay at the Latansa Bengkulu Hotel. Location has a positive effect on the customer's decision to stay at Hotel Latansa Bengkulu, thus the higher the location, the higher the customer's decision to stay at Hotel Latansa Bengkulu. Interior design has a positive effect on customer stay decisions. Service quality, location and interior design together show the influence on customer stay decisions at Hotel Latansa Bengkulu Keywords: Service Quality, Location, Interior Design, Decision,